Answer:
the answer should be a i hoped this helped\
Step-by-step explanation:
Answer:
d, e
Step-by-step explanation:
The applicable rules of exponents are ...
(a^b)(a^c) = a^(b+c)
a^-b = 1/a^b
__
In this case, it means the product is ...
(6^1)(6^0)(6^-3) = 6^(1+0-3) = 6^-2 = 1/6^2 = 1/36
__
The 6 without an exponent is equivalent to 6^1, an exponent of 1.
The sum of the exponents is -2.
Add the exponents to simplify the expression.
The value of the expression is 1/36.
An equivalent is any expression that results in 6^-2. One such is (6^5)(6^-7).
__
Only the last two choices, d and e, apply.
Answer:
the length of the missing side is 2
Step-by-step explanation:
Use a^2 + b^2 = c^2
a = 4
b = ?
c = 2sqrt5
4^2 + b^2 = (2sqrt5)^2
16 + b^2 = 20
subtract 16 from both sides
b^2 = 4
take the sqrt of both sides
b = 2
Answer:
Step-by-step explanation:
U need to think
Hello!
We are trying to describe the behavior of the graph given in the question.
To help us understand how to solve this question, we would need to understand <u>concavity.</u>
There are two types of concavity:
- Concave <em>up</em>
- Concave <em>down</em>
When a graph is concave up, the slope of the line would look like a "U".
When a graph is concave down, the slope of the line would look like a "U" that is flipped upside down.
In this case, we can see that the graph is concave down.
We can tell that the <em>slope</em> is negative due to the fact that the slope is going <u>down,</u> which results in the graph having a negative slope.
We can also tell that the graph is decreasing due to the fact that the line is doing downward.
Answer:
C). negative and decreasing